BULGARIAN FARMER'S PERCEPTION TOWARDS RISK - Hristina HARIZANOVA-BARTOS; Zornitsa STOYANOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The characteristics that influence farmer's behavior and attitude toward risk should be identified in order to explain inconsistencies between the farmer's perception of risk and the accurate measurement of the probability of the occurrence of a risk event. The article investigates the various types of responses of farmers to risk-related decisionmaking. The paper's goal is to highlight various types of farm characteristics in terms of risk and on this basis to be prepared general conclusions. The following tasks were assigned to achieve the goal: 1) a literature review is associated with the risk perception; 2) application of methodology for research the farmer’s behavior regarding their perceptions of risk taking; 3) determining and evaluating farm types; and 4) main conclusions and statements.